Information system to determine study programs for prospective students based on Android - Murti Retnowo; Ikrimach - (Compiler, 2022)
The development of information technology, especially the technology that exists on smartphones is very large, so many people have smartphones, with the existing smartphones at this time it can be used for various things, one of which is the determination of study programs for prospective new students. The selection of study programs that are permanent and in accordance with their abilities is one way for students to be able to complete their studies at universities. Many students are confused and careless in choosing a study program. There are also those who choose a study program only to go along with their friends so that during the lecture process there are many obstacles to achieve a bachelor's degree, even having to take education until the end of the study period. Multi Criteria Decision Making is one of the ways that can be used to help prospective students based on their own abilities, especially since the program is made specifically for Android-based Smartphones. Thus, prospective students can try to choose the best based on the values that match the criteria determined by the desired study program without being embarrassed to know whether to be accepted in the chosen study program or not. The use of the Android platform is because almost everyone now has an Android-based smartphone so that applications can be downloaded for free on the Play Store.